Long-term results from modified sphincteroplasty in patients with traumatic sphincter injury: a retrospective study - Berkesoglu, Mustafa; Colak, Tahsin; Turkmenoglu, Mehmet Ozgur; Han, Ismet; Kirmizi, Ilter; Akgul, Gokhan Giray; Gunduz, Ihsan (São Paulo Medical Journal, 2021)
BACKGROUND: The results from sphincteroplasty may worsen over time. Reseparation of the rectum and vagina/scrotum in conjunction with sphincteroplasty achieves good results. Improving the surgical effect of sphincteroplasty through perineal body reconstruction is crucial. OBJECTIVE: To evaluate the long-term results from anterior sphincteroplasty and perineal body reconstruction (modified sphincteroplasty) among patients with traumatic sphincter injury. DESIGN AND SETTING: Retrospective study among patients who underwent modified sphincteroplasty in a university hospital between January 2006 and December 2018. Fifty patients were evaluated in detail. METHODS: The following variables were evaluated: gender, age, additional disease status, time interval between trauma and surgery, surgical technique, duration of hospitalization, follow-up period after surgery, manometric values, electromyography results, magnetic resonance imaging scans, Wexner scores, satisfaction levels with surgery and surgical outcomes. RESULTS: The patients’ mean age was 44.6 ± 15.1 years. The median follow-up period was 62 months (range, 12-118). The mean Wexner scores preoperatively, postoperatively in first month (M1S) and at the time of this report (AAS) were 15.5 ± 3.2, 1.9 ± 3.15 and 3.9 ± 5.3, respectively. Although improvements in the patients’ mean Wexner scores became impaired over time, the postoperative Wexner scores were still significantly better than the preoperative Wexner scores (P = 0.001). CONCLUSION: Good or excellent results were obtained surgically among patients with traumatic sphincter injury. Performing perineal body reconstruction in addition to sphincteroplasty can provide better long-term continence. Surgical outcomes were found to be better, especially among patients younger than 50 years of age and among patients who underwent surgery within the first five years after trauma.